2008
DOI: 10.1007/s11064-008-9641-9
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine Uptake in Normal and Diabetic Rat Retina and Retinal Pigment Epithelium

Abstract: Diabetes-induced increase in oxidative stress is postulated as playing a significant role in the development of retinopathy. The retinal pigment epithelium (RPE) which forms part of the retinal blood barrier has been reported to be affected in diabetes. Besides functioning as a neurotransmitter, the radical nitric oxide (NO) can act as a cytotoxic agent. NO is synthesized by nitric oxide synthase (NOS) that oxidizes arginine to citrulline producing NO. Given that intracellular concentration of arginine depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…In this experimental condition, our results suggest that diabetes (or high glucose levels in cells derived form normoglycemic animals) exhibit a reduced L-arginine uptake, probably via CAT-1 and/or CAT-2B. In this regard, our results differ from previous studies where high glucose exposition was associated to an increased L-arginine transport in human umbilical vein endothelial cells (HUVEC) [34,35] or in retinal pigment epithelium [36]. Differences are attributed to cell type, as well as experimental conditions, since longer (hours) rather than rapid (minutes) exposition was used in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…In this experimental condition, our results suggest that diabetes (or high glucose levels in cells derived form normoglycemic animals) exhibit a reduced L-arginine uptake, probably via CAT-1 and/or CAT-2B. In this regard, our results differ from previous studies where high glucose exposition was associated to an increased L-arginine transport in human umbilical vein endothelial cells (HUVEC) [34,35] or in retinal pigment epithelium [36]. Differences are attributed to cell type, as well as experimental conditions, since longer (hours) rather than rapid (minutes) exposition was used in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Our results demonstrate that oxidative stress induced disassembly of vimentin intermediate filaments may cause vimentin phosphorylation in the RPE. L-Arginine uptake by RPE cells significantly increases the NO levels in diabetic rat RPE [40]. The current study implies dual roles of NO that 1 - 10 nmole·cm −2 ·min −1 of NO may protect RPE cell by PP2A and vimentin phosphorylation, whereas higher NO (>100 nmole·cm −2 ·min −1 ) generation under oxidative stress may induce apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study indicated that long-term use of L-citrulline is effective in the prevention of retinal vascular dysfunction induced by diabetes mellitus, and it may have a potential prophylactic effect in DR 21 . Nitric oxide synthase (NOS) could oxidize arginine to citrulline and induce the production of nitric oxide (NO), and diabetes upregulated NO levels in retinal pigment epithelium (RPE), indicating that NO may alter the function of RPE leading to DR pathogenesis 22 . As a regulating enzyme of arginine metabolism, arginase 2 participates in neurodegeneration during ROP pathogenesis, and deficiency of arginase 2 ameliorates the survival and function of neurons and reduces retinal neurodegeneration in vivo 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%